Penile Calciphylaxis in End Stage Renal Disease - Vincenzo Barbera; Luca Di Lullo; Antonio Gorini; Giovanni Otranto; Fulvio Floccari; Moreno Malaguti; Alberto Santoboni (Case Reports in Urology)
Calciphylaxis, better described as “Calcific uremic arteriolopathy” (CUA), involves about 1–4% of hemodialysis patients all around the world with high mortality rates. We describe a rare clinical case of CUA in peritoneal dialysis patient associated with urological disease. Penile calciphylaxis represents rare clinical complication, and an early diagnosis and multidisciplinary approach are requested. Pathogenesis is still unclear, and therapeutic approaches need more long-term clinical trials to test their efficacy and safety.